The Hampering Effect of Heavy Water (D2O) on Oscillatory Peptidization of Selected Proteinogenic α-Amino Acids - Fulczyk, Agnieszka; Łata, Eliza; Talik, Ewa; Kowalska, Teresa; Sajewicz, Mieczysław (Frontiers in Chemistry, 2020)
We present an overview of our studies on the hampering effect of heavy water (D2O) on spontaneous oscillatory peptidization of selected proteinogenic a-amino acids. The investigated set of compounds included three endogenous and two exogenous species. The experiments were carried out with use of high-performance liquid chromatography (HPLC), mass spectrometry (MS) and scanning electron microscopy (SEM). These techniques were chosen to demonstrate spontaneous oscillatory peptidization of a-amino acids in an absence of D2O (HPLC) and the hampering effect of D2O on peptidization (HPLC, MS and SEM). The HPLC analyses were carried out at 21±0.5 oC with each a-amino acid freshly dissolved in the binary liquid mixture of organic solvent + H2O, 70:30 (v/v) or in pure D2O for several dozen hours or several hours, respectively. The analyses with use of MS and SEM were carried out, respectively, after 7 days and one month of sample storage period in the darkness at 21±0.5 oC and for these experiments, each a-amino acid was dissolved in the liquid mixture of organic solvent + X, 70:30 (v/v), where X: H2O + D2O in volume proportions from 30:0 to 0:30. The results obtained with use of HPLC, MS and SEM point out to the strong hampering effect of D2O on the oscillations and peptidization yields, yet the dynamics of these processes significantly depends on chemical structure of a given a-amino acid.